Memory-Like Responses of Brain Microglia Are Controlled by Developmental State and Pathogen Dose - Lajqi, Trim; Stojiljkovic, Milan; Williams, David L.; Hudalla, Hannes; Bauer, Michael; Witte, Otto W.; Wetzker, Reinhard; Bauer, Reinhard; Schmeer, Christian (Frontiers in Immunology, 2020)
Microglia, the innate immune cells of the central nervous system feature adaptive immune memory with implications for brain homeostasis and pathologies. However, factors involved in emergence and regulation of these opposing responses in microglia have not been fully addressed. Recently, we showed that microglia from the newborn brain display features of trained immunity and immune tol-erance after repeated contact with pathogens in a dose-dependent manner. Here, we evaluated the impact of developmental stage on adaptive immune responses of brain microglia after repeated chal-lenge with ultra-low (1 fg/ml) and high (100 ng/ml) doses of the endotoxin LPS in vitro. We found that priming of naïve microglia derived from newborn but not mature and aged murine brain with ultra-low LPS significantly increased levels of pro-inflammatory mediators TNF-α, IL-6, IL-1β, MMP-9 and iNOS, as well as neurotrophic factors indicating induction of trained immunity (p < 0.05). In contrast, stimulation with high doses of LPS led to a robust down-regulation of pro-inflammatory cytokines and iNOS independently of the developmental state, indicating induced im-mune tolerance. Furthermore, high-dose priming with LPS upregulated anti-inflammatory mediators IL-10, Arg-1, TGF- β, MSR1 and IL-4. in newborn microglia (p < 0.05). Our data indicate pronounced plasticity of the immune response of neonate microglia compared with microglia derived from mature and aged mouse brain. Induced trained immunity after priming with ultra-low LPS doses may be responsible for enhanced neuroinflammatory susceptibility of immature brain. In contrast, the immunosuppressed phenotype following high-dose LPS priming might be prone to attenuate excessive damage after recurrent systemic inflammation.